Epididymal cysts in children: frequency, clinical characteristics, and management strategies - Cai, Wei; Liu, Chenchen; Xu, Lei; Wu, Qingtao; Kuang, Tongshuai; Lin, Xiaokun (Frontiers in Pediatrics, 2024)
Background: Epididymal cysts (ECs) are uncommon in the pediatric population. The objective of this study was to evaluate the frequency, clinical characteristics, and management strategies of ECs in children. Methods: We performed a retrospective review of pediatric scrotal ultrasounds between January 2014 and August 2022 to identify children with ECs. Results: One hundred and forty-three children boys were found to have ECs, with 95 being pre-pubertal and 48 post-pubertal. The age of the patients ranged from 1 day to 18 years, with a mean age of 10.64±4.55 years. The size of the cysts varied from 2 mm to 35 mm. The most common comorbidities observed were hydrocele, testicular microlithiasis and varicocele. The majority of ECs were detected through routine physical examination. Conservative management was employed for all patients, except for one who required surgical excision. Resolution of ECs occurred in 12 patients, while a reduction in cyst size was observed in 6 cases. Conversely, 2 patients experienced an increase in cyst size, and 6 patients exhibited an increase in cyst number during the follow-up period. Conclusion: Conservative management is the preferred approach for the majority of cases, with surgical intervention reserved for specific instances.